PENGARUH EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) TERHADAP PERILAKU PENCEGAHAN COVID-19 PADA ANAK USIA SEKOLAH - Sri Aminingsih; Endang Dwi Ningsih (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2022)
Background. According to the Ministry of Health of the Republic of Indonesia (2020), the age group of children is very vulnerable to being infected with COVID-19. Classification of children aged less than 18 years with a total number of children as many as 79.5 million or 30.1% of confirmed cases of positive COVID-19 children. The percentage is 8,1% positive for COVID-19, 8,6% being treated, 8,3% recovering, and 1,6% dying. In an effort to maintain the health of children, the Indonesian Ministry of Health has determined several preventions for COVID-19, which include implementing a clean and healthy lifestyle (washing hands with soap, using a mask when coughing or colds, exercising regularly, getting enough rest and consuming a balanced diet with lots of vegetables and fruits). fruit). A clean and healthy lifestyle must be applied as early as possible so that it becomes a positive habit in maintaining health. SDN 01 Malanggaten is a public elementary school located in the east of the Kebakramat sub-district. The number of students from grades 4 to 6 is approximately 60 students. Based on information from the Indonesian Ministry of Health (2020), school-age children are very vulnerable to COVID-19, so it is necessary to implement as early as possible about PHBS education and prevention of covid-19 so that children avoid the disease covid-19. The Purpose. To determine the effect of education on clean and healthy living behavior (PHBS) on the behavior of preventing COVID-19 in school-age children Method. This study is a post-test, pre-post test and the static group comparison design research to determine the effect of clean and healthy living behavior education (PHBS) on covid-19 prevention behavior in school-age children, the results of the study using Paired T-Test Results. Mean before education 12,2750 and after education 15.1000, mean differences -2,82500, std deviation 2,70695 . Based on the value of the mean difference (mean differences) is negative, namely -2,82500, it can be interpreted that the result after being given education is higher than before being given education, with sig. (2-tailed) p value = 0,001. The Conclusion. PHBS behavior education is significantly effective for improving Covid-19 prevention behavior Keywords PHBS Education, Covid-19 prevention behavior in children